Preparation of graphene oxide/polyacrylonitrile fiber from graphene oxide solution with high dispersivity. Issue 2 (1st February 2020) - Li, Changqing; Wang, Xiaoli; Xu, Lianghua; Gao, Aijun; Xu, Dehua
ABSTRACT: This paper reports the grafting of polyacrylonitrile (PAN) onto the functional groups of graphene oxide (GO) by bridge linkers, toluene diisocyanate (TDI) in high concentration GO solution to prepare GO/PAN composite fiber. In this study, it was discovered that GO solution with high dispersivity is rich in oxygen-containing functional groups and the well-dispersed GO exists as multi-layer graphenes and does not display liquid crystallinity. These factors contribute to the high dispersivity of the GO solution and spinning difficulty. To overcome these issues, TDI was used to bridge the easily spinnable PAN and rich oxygen-containing functional groups in GO. IR spectra confirmed that the TDI successfully linked PAN and GO with enhanced binding. Wet spinning was then used to spin the bridge-linked GO solution into GO/PAN composite fiber. SEM and Raman spectroscopy were used to characterize the fiber surface and carbon structure, respectively. The GO/PAN composite fiber prepared by wet spinning in an ethanol coagulation bath exhibited less folding, higher compactness, a lower degree of structural defects, and a uniform distribution of high GO content in the fiber. The interconnected graphene network shows potential for application as a graphene-based composite fiber with high thermal conductivity. GRAPHICAL ABSTRACT: